Ictiofauna de la pesquería ribereña en Bahía de Navidad, Jalisco, México, asociada al evento El Niño 1997-1998 - Rojo-Vázquez, J A (2001)
The ichthyofauna fished in Bahía de Navidad, Jalisco, Mexico in the Central Pacific was surveyed during 1998. Six thousand nine hundred and fourty-four organisms of 130 species were caught which weighted 3 231 kg. Nearly 30 % of the species belonged to Carangidae, Haemulidae and Sciaenidae. The most important species in number and biomass were Microlepidotus brevipinnins, Caranx caninus and C. caballus. Species number, abundance and biomass fluctuated during the year. The largest number of species was caught in June (61), the minimum in March (33). January had the maximum abundance (1 397 organisms), while the minimum was obtained during August (251). The maximum biomass values were from January (556.5 kg), and the lowest from August (114.7 kg). Eighteen species accumulated 87 % of the total abundance, while 20 species represented 86.3 % of the biomass. There were large in differences species number, abundance and biomass nets of different mesh size.